Global proteomic profiling of multiple organs of cats (Felis catus) and proteome-transcriptome correlation during acute Toxoplasma gondii infection - Lan-Bi Nie; Wei Cong; Jun-Jun He; Wen-Bin Zheng; Xing-Quan Zhu (BMC, 2022)
Abstract Background Toxoplasma gondii is a protozoan parasite which can infect almost all warm-blooded animals and humans. Understanding the differential expression of proteins and transcripts associated with T. gondii infection in its definitive host (cat) may improve our knowledge of how the parasite manipulates the molecular microenvironment of its definitive host. The aim of this study was to explore the global proteomic alterations in the major organs of cats during acute T. gondii infection. Methods iTRAQ-based quantitative proteomic profiling was performed on six organs (brain, liver, lung, spleen, heart and small intestine) of cats on day 7 post-infection by cysts of T. gondii PRU strain (Genotype II). Mascot software was used to conduct the student's t-test. Proteins with P values < 0.05 and fold change > 1.2 or < 0.83 were considered as differentially expressed proteins (DEPs). Results A total of 32,657 proteins were identified in the six organs, including 2556 DEPs; of which 1325 were up-regulated and 1231 were down-regulated. The brain, liver, lung, spleen, heart and small intestine exhibited 125 DEPs, 463 DEPs, 255 DEPs, 283 DEPs, 855 DEPs and 575 DEPs, respectively. Gene Ontology (GO) annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses of all proteins and DEPs in all organs showed that many proteins were enriched in binding, cell part, cell growth and death, signal transduction, translation, sorting and degradation, extracellular matrix remodeling, tryptophan catabolism, and immune system. Correlations between differentially expressed proteins and transcripts were detected in the liver (n = 19), small intestine (n = 17), heart (n = 9), lung (n = 9) and spleen (n = 3). Conclusions The present study identified 2556 DEPs in six cat tissues on day 7 after infection by T. gondii PRU strain, and functional enrichment analyses showed that these DEPs were associated with various cellular and metabolic processes. These findings provide a solid base for further in-depth investigation of the complex proteotranscriptomic reprogramming that mediates the dynamic interplays between T. gondii and the different feline tissues.